Luis Emilio Recabarren. Escritos de Prensa, 1898-1924 - Cruzat, Ximena; Deves, Eduardo (Ariadna Ediciones, 2016)
Full Compilation press articles the Chilean labor leader L E Recabarren; Chilean socialism, Latin American socialism in the early twentieth century
Spanish; Castilian
Keywords: Latin America; History; chile; history; political; working press